2015
DOI: 10.1007/s00425-015-2402-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of postharvest strawberry fruit in response to exogenous auxin and abscisic acid

Abstract: Auxin and abscisic acid regulate strawberry fruit ripening and senescence through cross-talk of their signal transduction pathways that further modulate the structural genes related to physico-chemical properties of fruit. The physiological and transcriptomic changes in harvested strawberry fruits in responses to IAA, ABA and their combination were analyzed. Exogenous IAA delayed the ripening process of strawberries after harvest while ABA promoted the postharvest ripening. However, treatment with a combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 53 publications
6
66
0
1
Order By: Relevance
“…Earlier, fruit softening related gene expression has been studied extensively in strawberry having also a short shelf life. Indications that ABA activates expression of FaPL, FaCEL, FaRGlyase, FcXTH1, Fa β Gal4, FaXYL1 and expansins have been reported (Bustamante et al, 2009; Molina-Hidalgo et al, 2013; Opazo et al, 2013; Chen et al, 2016; Medina-Puche et al, 2016; Paniagua et al, 2016). However, earlier studies have shown that the textural changes occurring during fruit ripening are characteristic to particular fruit species, and are due to differences in type and extent of cell wall modifications and the expression of the modifying enzymes during ripening (Goulao and Oliveira, 2008; Payasi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier, fruit softening related gene expression has been studied extensively in strawberry having also a short shelf life. Indications that ABA activates expression of FaPL, FaCEL, FaRGlyase, FcXTH1, Fa β Gal4, FaXYL1 and expansins have been reported (Bustamante et al, 2009; Molina-Hidalgo et al, 2013; Opazo et al, 2013; Chen et al, 2016; Medina-Puche et al, 2016; Paniagua et al, 2016). However, earlier studies have shown that the textural changes occurring during fruit ripening are characteristic to particular fruit species, and are due to differences in type and extent of cell wall modifications and the expression of the modifying enzymes during ripening (Goulao and Oliveira, 2008; Payasi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous application of ABA has been shown in many studies to advance especially non-climacteric fruit ripening and the associated anthocyanin accumulation in grape berries (Wheeler et al, 2009; Koyama et al, 2010; Villalobos-González et al, 2016), strawberries (Chai et al, 2011; Jia et al, 2011; Kadomura-Ishikawa et al, 2015; Chen et al, 2016), sweet cherries (Luo et al, 2014; Shen et al, 2014), and litchi fruit (Wei et al, 2011; Singh et al, 2014). Moreover, treatments with inhibitors of ABA biosynthesis, such as fluridone and nordihydroguaiaretic acid (NDGA), delay fruit ripening and decrease anthocyanin accumulation (Jia et al, 2011; Shen et al, 2014; Kadomura-Ishikawa et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown that auxin suppresses anthocyanin biosynthesis in the red-fleshed apple callus [43]. Endogenous expression of auxin [44, 45] has been found to impede anthocyanin accumulation in strawberries. In additional, cytokinins are also known to play an important role in anthocyanin biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Fruit ripening is associated with auxin signaling involved in the postharvest storage of fruits [28]. The elucidation of how AUX/IAA-mediated auxin signaling function in postharvest decay is therefore of importance to both plant biologists and agronomists [29]. In the present work, we provide comprehensive information on the genomic structures, sequence homology levels and expression patterns of Aux/IAA genes in papaya.…”
Section: Introductionmentioning
confidence: 99%